Effects of a mindfulness-based interventions on stress, burnout in nurses: a systematic review and meta-analysis - Wang, Qi; Wang, Fang; Zhang, Shurong; Liu, Chaofan; Feng, Yue; Chen, Junzhu (Frontiers in Psychiatry, 2023)
Background: Stress in the healthcare environment causes negative effects in nurses such as burnout, anxiety, and depression. The COVID-19 pandemic has resulted in increased pressure on medical staff globally, highlighting the potential benefits of mindfulness-based interventions in reducing nurses' stress levels. Despite numerous studies exploring the effect of mindfulness-based training on nurses, the results remain inconclusive.Objective: To systematically evaluate the impact of mindfulness training on nurse's performance and increase the certainty of existing evidence.